PC.40 Assessment of Myocardial Performance using Novel Echocardiography Markers in Infants less than 29 Weeks Gestation during the Transitional Period. (9th June 2014) - James, A; Corcoran, D; Jain, A; Mertins, L; McNamara, P; Franklin, O; El-Khuffash, A
Abstract : Introduction: Physiological changes of the preterm heart during the transitioning period are a challenging area to assess. Colour Tissue Doppler derived longitudinal strain (LS) and strain rate (SR) as well as tricuspid annulus plane systolic excursion (TAPSE) and fractional area change (FAC) are novel echocardiographic techniques for the assessment of left (LV) and Right (RV) ventricular function. We aimed to assess the feasibility and reliability of measuring these indices in preterm infants less than 29 weeks gestation during the transitioning period. Methods: A prospective study was conducted on 54 preterm infants, with a mean (SD) gestation and birth weight of 26.7 (1.4) weeks and 954 (231) grams. LS, SR, conventional markers and novel RV markers were measured at a mean of 10 and 45 h of life. Reliability was assessed by using intra class correlation coefficient (ICC) and Bland-Altman Analysis. Results: Despite no significant change in conventional markers such as shortening fraction or ejection fraction, there was a significant increase in septal SR(-1.6 to -1.8, p = 0.002) and SRE(1.7 to 2.2, p = 0.002) across the two time points. RV function parameters including SR, SRA, TAPSE, and FAC demonstrated a significant increase across the two time points. Septal and RV function and dimension parameters demonstrated excellent reliability results. Conclusion: Myocardial deformation including strain, strain rate was as well as RV markers and dimensions were feasible in infants less than 29 weeks gestation. Significant changes were seen using novel echocardiographic markers over the transitional period.